A general catch comparison method for multi-gear trials: application to a quad-rig trawling fishery for Nephrops. (22nd January 2017) - Browne, D.; Minto, C.; Cosgrove, R.; Burke, B.; McDonald, D.; Officer, R.; Keatinge, M.
Abstract : Expeditious uptake of quad-rig trawling in the economically important Irish fishery for Nephrops norvegicus outpaced technical understanding of this newly introduced gear. The main driver for its introduction is increased catch rates of Nephrops . Higher Nephrops discard rates associated with quad-rig trawling are likely to be problematic under the landing obligation unless size selectivity can be improved. Catch comparison methods are suitable for assessing the performance of fishing gear modifications to reduce discards. Utilizing a quad-rig potentially increases the number of gears that can be included in a catch comparison study to four but current modeling methods are limited to two gears. Our study provides a new general multinomial mixed effects modeling framework that can be applied to two or more gears, elucidates how case-specific and choice-specific covariates may influence catch at length, and facilitates discussion on appropriate gear based management measures. Application of the method to catches from four different cod-end mesh sizes revealed significant effects of carapace length, catch weight and net position, on the numbers of Nephrops retained in each cod-end. Results suggest that management measures which specifically address different catch profiles associated with different numbers of trawling rigs are required to optimize Nephrops size selectivity.